Agreement between observational and necropsy-derived diagnosis for cause of death for cattle in a commercial beef feedlot - Anspaugh, D.; Wileman, Benjamin W.; Apley, M.; Taylor, W.; Noffsinger, T.; Thomson, Daniel U.; Reinhardt, Christopher D. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2012)
Necropsy information is an integral component for monitoring feedlot disease and designing preventive and therapeutic strategies; however, field necropsy is a laborious and time-consuming procedure and may be an occupational hazard because personnel can become injured or be exposed to zoonotic disease while conducting necropsies. The objective of this study was to determine the accuracy of a pre-necropsy mortality diagnoses made by feedlot personnel compared with diagnoses made from necropsy results.
Keywords: Beef; Necropsy; Feedlot; Feedlot diseases